Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

What are the roots of the equation?
10x2 - 6x + 4 = -3x


Sagot :

Answer:

(3 +/- i*sqrt(151) / 20 (no real solutions)

Step-by-step explanation:

10x^2 - 6x + 4 = -3x

Add 3x to both sides

10x^2 - 6x + 4 + 3x = -3x + 3x

10x^2 - 6x + 4 + 3x = 0

Add like terms

10x^2 - 3x + 4 = 0

We have to use quadratic formula to find the answers

For this equation, a = 10, b = -3 and c = 4

Note: +/- is plus or minus

Quadratic formula:

x = (-b +/- sqrt(b^2 - 4ac)) / 2a

x = (-(-3) +/- sqrt(-3^2 - 4(10)(4))) / 2(10)

x = (3 +/- sqrt(9 - 160)) / 20

x = (3 +/- sqrt(-151) / 20

x = (3 +/- i*sqrt(151) / 20

if there's a "-" sign inside a square root, it will give you an imaginary number.

Example:

-sqrt(9) = -3

sqrt(-9) = 3i (first you will ignore the "- " sign, then square the number. After finding the square root, take that '-' sign and turn it to an "i")

So for sqrt(-151), 151 is not a perfect square, so you will get a decimal number. Leave it as it is:

sqrt(151). We can't forget about the "-". Turn the minus into a sign.

It will be i*sqrt(151)

Imaginary numbers can't be simplified, so this is the answer.

(3 +/- i*sqrt(151) / 20

Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.